Whole-Genome Analyses Reveal Genomic Characteristics and Selection Signatures of Lincang Humped Cattle at the China–Myanmar Border - Sun, Luyang; Qu, Kaixing; Ma, Xiaohui; Hanif, Quratulain; Zhang, Jicai; Liu, Jianyong; Chen, Ningbo; Suolang, Quji; Lei, Chuzhao; Huang, Bizhi (Frontiers in Genetics, 2022)
The location on the Yunnan border with Myanmar and its unique cultural landscape have shaped Lincang Humped cattle over time. In the current study, we investigated the genetic characteristics of 22 Lincang Humped cattle using whole-genome resequencing data. We found that Lincang Humped cattle derived from both Indian indicine and Chinese indicine cattle depicting higher levels of genomic diversity. Based on genome-wide scans, candidate genomic regions were identified that were potentially involved in local thermal and humid environmental adaption, including genes associated with the body size (TCF12, SENP2, KIF1C, PFN1), immunity (LIPH, IRAK3, GZMM, ELANE) and heat tolerance (MED16, DNAJC8, HSPA4, FILIP1L, HELB, BCL2L1, TPX2). Missense mutations were detected in candidate genes IRAK3, HSPA4 and HELB. Interestingly, eight missense mutations observed in the HELB gene were specific to the indicine cattle pedigree. These mutations may reveal differences between indicine and taurine cattle adapted to variable climatic conditions. Our research provides new insights into the genetic characteristics of Lincang Humped cattle representing Lincang and Pu’er areas as an important channel for the migration of Indian indicine from domestication centers toward southwestern China.